A Hackathon for Classical Tibetan - Orna Almogi; Lena Dankin; Nachum Dershowitz; Lior Wolf (Journal of Data Mining and Digital Humanities, 2019)
We describe the course of a hackathon dedicated to the development of linguistic tools for Tibetan Buddhist studies. Over a period of five days, a group of seventeen scholars, scientists, and students developed and compared algorithms for intertextual alignment and text classification, along with some basic language tools, including a stemmer and word segmenter.